The Effect of Physical Education on Improving College Students' Mental Health in the Context of Curriculum Ideology and Politics - Jiang Hui; Shen Xin; Chen Cheng, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This research centres on college students and investigates the influence of diverse physical exercise regimens on distinct facets of their mental well-being. Prior scholarship indicates a positive correlation between physical exercise and the mental health enhancement of college students. Physical exercise has been shown to regulate emotions, bolster mental well-being, and mitigate anxiety and depression. Consequently, the primary aim of this study was to scrutinize the impact of physical education on augmenting the mental health of college students within the framework of curriculum ideology and politics. This academic inquiry delves into the ramifications of engaging in three distinct sports activities—basketball, taijiquan, and cheerleading—on the mental well-being of female collegiate participants. The study scrutinizes the impact of exercise duration, exercise cycle, and exercise frequency on various psychological health parameters. Data were meticulously organized and subjected to analysis through the statistical software SPSS 11.5. Employing t-tests and one-way ANOVA, the study examines the psychological health indicators across the three distinct exercise programs, discerning the significance of disparities therein. Upon comparing the psychological health statuses of students before and after engaging in Taijiquan exercises, notable variances emerged across four dimensions: anxiety, terror, paranoia, and psychosis. Particularly noteworthy were the substantial disparities observed in the paranoia dimension. Cheerleading, a sport amalgamating dance and physical fitness set to music, serves as a fervently embraced pursuit among students, symbolizing zeal, youthfulness, and vivacity. Implications and engaging in basketball, Taijiquan, and cheerleading exercises has been found to be efficacious in alleviating anxiety levels among college students. Taijiquan, in particular, exhibits a distinctive efficacy in ameliorating paranoid tendencies, while cheerleading exercises manifest a superior spectrum of improvement factors compared to basketball and Taijiquan routines. Tailoring physical exercise programs to college students' age, gender, and psychological predispositions is imperative for optimizing mood enhancement and overall mental well-being. Individual psychological needs may vary across different time periods, underscoring the importance of selecting appropriate exercise modalities accordingly. Integration of these exercise regimens into university physical education curricula necessitates an augmented allocation of instructional hours, facilitating students' acquisition of requisite skills for autonomous exercise. This approach empowers college students to proficiently utilize their sports acumen and abilities for self-directed physical activity during leisure time, thereby augmenting the efficacy of physical exercise in advancing collegiate health outcomes.